1975
DOI: 10.1210/jcem-41-2-395
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroxine and Thyroxine-Binding Proteins in Chronic Renal Failure Without Nephrosis

Abstract: Total serum thyroxine (T4), free thyroxine index (FTI), thyroxine binding globulin (TBG) binding capacity, serum albumin, alpha-globulins and urinary protein excretion were measured in 50 patients with chronic renal failure, but without nephrotic syndrome. 25 patients were undergoing chronic hemodialysis. T4 was within the normal range in most patients. There was a tendency to lower T4 values as compared to an age and sex-matched control group, but this did not reach statistical significance. TBG was normal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
5
14
0
Order By: Relevance
“…We found that serum TT4 concentrations, although within the normal range, tended to be lower than in controls, in agreement with the findings of other investigators (5,14,33,46). Neuhaus et al (46) attributed the low TT4 to decreased serum albumin and prealbumin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that serum TT4 concentrations, although within the normal range, tended to be lower than in controls, in agreement with the findings of other investigators (5,14,33,46). Neuhaus et al (46) attributed the low TT4 to decreased serum albumin and prealbumin.…”
Section: Discussionsupporting
confidence: 93%
“…After TRH injection, serum TSH concentration rose rapidly in seven normal subjects, reached a peak by 30 min, and returned to basal levels in 3 h. Of the seven HD patients tested, one showed no increase in serum TSH concentration, four had a blunted response, and the other two showed a low normal response. In the latter, the peak was delayed until [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] min, and TSH levels remained elevated for more than 3 h (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased levels of T4 may be secondary to the protein loss, which occur in CRF. Serum albumin and thyroid binding pre-albumin decreases 17 . Decrease in T4 is also attributed to the presence of circulating inhibitors, which impairs binding of T4 to thyroxine binding globulin.…”
Section: Discussionmentioning
confidence: 96%
“…The findings are comparable with previous study. 14,15,16,17 . The different studies mentioned various reasons to decreased levels of T4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation